Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1177/1468087419844398
|View full text |Cite
|
Sign up to set email alerts
|

A new comprehensive tribo-dynamic analysis for lubricated translational joints in low-speed two-stroke marine engines

Abstract: In low-speed two-stroke marine engines, the effect of connecting rod inertia is important for the tribo-dynamics of crosshead slipper-guide and piston skirt-liner. However, this has not been considered in previous research. Therefore, a new tribo-dynamic model that considers the connecting rod inertia is presented for the two lubricated translational joints, and the lubricant viscosity–temperature properties are accurately incorporated into the model. The modified extended backward differentiation formulate me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 46 publications
2
35
0
Order By: Relevance
“…In our previous study, we established a tribo-dynamic model that couples the dynamics of the crosshead assembly, piston assembly, and connecting rod with the crosshead slipper-guide and piston skirt-liner friction pairs. Under the engine rated conditions, an analysis of the tribo-dynamics of the crosshead slipper has been carried out [4,12,29,30]. In our previous study, the crankshaft speed was set to a fixed value.…”
Section: Mathematical Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…In our previous study, we established a tribo-dynamic model that couples the dynamics of the crosshead assembly, piston assembly, and connecting rod with the crosshead slipper-guide and piston skirt-liner friction pairs. Under the engine rated conditions, an analysis of the tribo-dynamics of the crosshead slipper has been carried out [4,12,29,30]. In our previous study, the crankshaft speed was set to a fixed value.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Internal friction refers to the friction generated by various machines inside the ship, and external friction refers to the friction generated between the hull and the ocean. Research results have indicated that the friction loss of marine diesel engines is the primary source of internal friction [2][3][4]. To deal with a shortage of energy and environmental protection issues [5][6][7][8][9], the development of low-friction technology for marine diesel engines has become an urgent requirement of engine manufacturers.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations